Kecurangan KERANGKA YURIDIS STRATEGI PENCEGAHAN FRAUD DALAM PELAKSANAAN INVESTASI PEMERINTAH DAERAH DALAM RANGKA MEWUJUDKAN GOOD GORVENANCE DI KABUPATEN MALANG : - - Solehuddin, Solehuddin; Bagaskoro , Ladito Risang; Arrsa , Ria Casmi (Mendapo: Journal of Administrative Law, 2023)
Implementation of Local Government Investments plays an important and strategic role in accelerating economic growth and improving services to the public. The position of Malang Regency as the implementation of Regional Government is by the provisions of Law Number 23 of 2014 concerning Regional Government. The authority of Malang Regency Government includes regulation, operation and supervision. The juridical framework for fraud prevention strategies in implementing Local Government investment in order to realize good governance in Malang Regency has not been implemented in investment practices in 4 (four) BUMDs including Perumda Tirta Kanjuruhan, BPR Artha Kanjuruhan, PD Jasa Yasa, Bank Jatim. The absence of a feasibility analysis, portfolio analysis and risk analysis has the potential for fraudulent practices in the implementation of investment (Equity Participation) of the Regional Government so that the implementation of investment will be at odds with the efforts of the Malang Regency Government to realize good governance.